Raspberry Pi For Kids - Richard Wentk (Willey, 2015)
Review“Remembering the intended target audience, the inevitable setting up chapters are both necessary and well judged, with details on cables and other information to enable younger makers to get going without adult help. Ignoring the ‘For Kids’ branding, this book would be a valuable start for any nervous adult computer user keen to gain Pi enlightenment.” (MagPi, September 2015)